Portaria PGR/MPF nº 55, de 29 de janeiro de 2018 - Raquel Elias Ferreira Dodge (DOU, Brasília, DF, 6 fev. 2018. Seção 2, p. 49., 2018)
Revoga, a pedido, a Portaria PGR/MPF nº 108, de 25 de fevereiro de 2016.